2021
DOI: 10.7554/elife.60317
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin-expressing parafacial neurons are CO2/H+ sensitive and regulate baseline breathing

Abstract: Glutamatergic neurons in the retrotrapezoid nucleus (RTN) function as respiratory chemoreceptors by regulating breathing in response to tissue CO2/H+. The RTN and greater parafacial region may also function as a chemosensing network composed of CO2/H+-sensitive excitatory and inhibitory synaptic interactions. In the context of disease, we showed that loss of inhibitory neural activity in a mouse model of Dravet syndrome disinhibited RTN chemoreceptors and destabilized breathing (Kuo et. al., 2019; 25). Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…In addition, there were neurons that were inhibited by hypercapnia (I). Inhibition of RTN neuronal firing by hypercapnia has been previously observed ( Cleary et al, 2021 ; Nattie et al, 1993 ; Ott et al, 2011 ).…”
Section: Discussionmentioning
confidence: 74%
“…In addition, there were neurons that were inhibited by hypercapnia (I). Inhibition of RTN neuronal firing by hypercapnia has been previously observed ( Cleary et al, 2021 ; Nattie et al, 1993 ; Ott et al, 2011 ).…”
Section: Discussionmentioning
confidence: 74%
“…For example, in the context of Dravet syndrome (caused by loss of function mutations in SCN1A), we showed that Scn1a transcript is expressed by inhibitory parafacial neurons in the region of the RTN (Kuo et al, 2019). We also showed that inhibitory somatostatin (SST)-expressing neurons in the region of the RTN are inhibited by CO 2 /H + and contribute to RTN chemoreception by disinhibition of CO 2 /H + -activated glutamatergic neurons (i.e., RTN chemoreceptors; Cleary et al, 2021). Therefore, in addition to causing cortical seizure activity, Dravet syndrome-associated Scn1a mutations may disrupt the inhibitory modulation of RTN chemoreception.…”
Section: Direct Effect Of Epilepsy Associated Mutations On Brainstem ...mentioning
confidence: 97%
“…In this study, to determine the relative contribution of the RTN neuronal population to the hypercapnic respiratory J Physiol 602.1 response, we used a viral vector with a pan-neuronal promoter. We did not target the specific subpopulation of RTN neurons that express the specific markers of the chemosensitive neurons, and inhibition of other neurons within the region could potentially have changed the respiratory response to CO 2 (Cleary et al, 2021). The physiological data showing complete blockade of active expirations and significant (by ∼40%) reduction in the inspiratory response to CO 2 were found to be very similar to that reported in the preceding studies (Marina et al 2010;Nattie & Li, 2002Takakura et al, 2014), suggesting that a critical number of RTN neurons were successfully inhibited in these experiments.…”
Section: Experimental Limitationsmentioning
confidence: 99%